EJNMMI physics - European Association of Nuclear Medicine (Springer-Verlag, GmbH, 2014)
"EJNMMI Physics is an international platform for scientists, users and adopters of nuclear medicine with a particular interest in physics matters. As a companion journal to the European Journal of Nuclear Medicine and Molecular Imaging, this journal has a multi-disciplinary approach and welcomes original materials and studies with a focus on applied physics and mathematics as well as imaging systems engineering and prototyping in nuclear medicine. This includes physics-driven approaches or algorithms supported by physics that foster early clinical adoption of nuclear medicine imaging and therapy."
Keywords: Nuclear medicine : Periodicals; Nuclear physics : Periodicals; Diagnostic imaging : Periodicals; Nuclear Medicine; Nuclear Physics; Diagnostic Imaging; Diagnostic Techniques, Radioisotope; Radioisotopes : therapeutic use; Diagnostic imaging; Nuclear medicine; Nuclear physics